Absorption of isobutane in three linear chained pentaerythritol esters between 293.15 and 348.15 K. (April 2017) - Sun, Yanjun; Wang, Xiaopo; Wang, Dongbo; Jin, Liwen; Liu, Zhigang
Highlights: The absorption properties of R600a in PEC4, PEC6, and PEC8 have been measured based on the isochoric method. The data were correlated using the PR EoS with HVOS mixing rules and Wilson equation. The absorption properties of R600a in PEC4, PEC5, PEC6, PEC7, and PEC8 are discussed. Abstract: Isobutane (R600a) is widely used in small capacity refrigeration equipment, especially domestic refrigerator. Knowledge of refrigerant absorption in lubricant oil is one of the essential factors for designing refrigeration system and choosing suitable oil. In this work, the liquid mole fractions of R600a in three linear chained pentaerythritol esters (pentaerythritol tetrabutyrate, pentaerythritol tetrahexanoate, and pentaerythritol tetraoctanoate) were measured from 293.15 K to 348.15 K by means of isochoric saturation method. The measured data were modeled using the PR EOS and HVOS mixing rule combined with Wilson excess free-energy model. Average relative deviations between the calculated pressure from the model and measured results for R600a + pentaerythritol tetrabutyrate, R600a + pentaerythritol tetrahexanoate, and R600a + pentaerythritol tetraoctanoate systems were 0.74%, 0.90%, and 0.57%, respectively. Maximum relative deviations were 2.13%, 2.91%, and 2.13%, respectively.